Procyanidins Extracted from Lotus Seedpod Ameliorate Amyloid-β-Induced Toxicity in Rat Pheochromocytoma Cells. (28th October 2018) - Huang, Hao; Yan, Peipei; Sun, Taoping; Mo, Xiaoxing; Yin, Jiawei; Li, Peiyun; Zhu, Yalun; Rong, Shuang; Yang, Wei; Chen, Xiaoyi; Liu, Liegang
Abstract : Alzheimer's disease (AD) is a progressive neurodegenerative disease, which is characterized by extracellular senile plaque deposits, intracellular neurofibrillary tangles, and neuronal apoptosis. Amyloid- β (A β ) plays a critical role in AD that may cause oxidative stress and downregulation of CREB/BDNF signaling. Anti-A β effect has been discussed as a potential therapeutic strategy for AD. This study aimed to identify the amelioration of procyanidins extracted from lotus seedpod (LSPC) on A β -induced damage with associated pathways for AD treatment. Rat pheochromocytoma (PC12) cells incubated with A β 25–35 serve as an A β damage model to evaluate the effect of LSPC in vitro . Our findings illustrated that LSPC maintained the cellular morphology from deformation and reduced apoptosis rates of cells induced by A β 25–35 . The mechanisms of LSPC to protect cells from A β -induced damage were based on its regulation of oxidation index and activation of CREB/BDNF signaling, including brain-derived neurotrophic factor (BDNF) and phosphorylation of cAMP-responsive element-binding (CREB), protein kinase B (also known as AKT), and the extracellular signal-regulated kinase (ERK). Of note, by high-performance liquid chromatography-tandem mass spectroscopy (LC-MS/MS), several metabolites were detected to accumulate in vivo, part of which could take primary responsibility for the amelioration of A β -induced damage on PC12 cells. Taken together, our research elucidated the effect of LSPC on neuroprotection through anti-A β, indicating it as a potential pretreatment for Alzheimer's disease.